2019
DOI: 10.1002/anie.201907901
|View full text |Cite
|
Sign up to set email alerts
|

Constrained Peptides with Fine‐Tuned Flexibility Inhibit NF‐Y Transcription Factor Assembly

Abstract: Protein complex formation depends on the interplay between preorganization and flexibility of the binding epitopes involved. The design of epitope mimetics typically focuses on stabilizing a particular bioactive conformation, often without considering conformational dynamics, which limits the potential of peptidomimetics against challenging targets such as transcription factors. We developed a peptide‐derived inhibitor of the NF‐Y transcription factor by first constraining the conformation of an epitope throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 58 publications
(20 reference statements)
1
28
0
Order By: Relevance
“…Ar elated observation was recently described in studies on con-strainedi nhibitors of transcriptionf actor assembly where subtle changes to structure were observed to affect the stability of the bound state. [81] The resultsp resented here for HIF-1a 812-826 sE816C-R820Cd iffer;w hilst am oderate increase in helicity might make ac ontribution to enhanced p300 binding and ligand induced changes in p300 conformation cannot be discounted, our data reveal the potential toe nhance target bindinga ffinity of constrained peptidesb yexplicit stabilization of ab ound conformation ( Figure S8). The results add to the complex effects on molecular recognition that can arise upon constraining ap eptidew hich include enthalpy-entropyc ompensation, induced-fit recognition, [82] modulating binding mechanism and dynamics.…”
Section: Discussionmentioning
confidence: 65%
“…Ar elated observation was recently described in studies on con-strainedi nhibitors of transcriptionf actor assembly where subtle changes to structure were observed to affect the stability of the bound state. [81] The resultsp resented here for HIF-1a 812-826 sE816C-R820Cd iffer;w hilst am oderate increase in helicity might make ac ontribution to enhanced p300 binding and ligand induced changes in p300 conformation cannot be discounted, our data reveal the potential toe nhance target bindinga ffinity of constrained peptidesb yexplicit stabilization of ab ound conformation ( Figure S8). The results add to the complex effects on molecular recognition that can arise upon constraining ap eptidew hich include enthalpy-entropyc ompensation, induced-fit recognition, [82] modulating binding mechanism and dynamics.…”
Section: Discussionmentioning
confidence: 65%
“…69 Initially, incorporation of an i, i + 4 a-methyl, a-alkenyl hydrocarbon staple was shown to reduce the binding affinity of a native, 19-residue NF-YA peptide for the NF-YB/C dimer, despite increasing the helicity of the free peptide in solution from 13% to 47%. 70 In contrast a shorter 16residue analogue bearing the exact same constraint had signicantly higher affinity. Since the precise implications of amethylation remain unclear, the group expanded their study to explore whether the a-methyl groups caused the loss of affinity upon peptide elongation.…”
Section: The Staple Structure: Inuence On Peptide Conformation and Tmentioning
confidence: 99%
“…The intriguing result was found to derive exclusively from the conformational characteristics of the bound peptides; a combination of 2D 1 H– 1 H TOCSY and transfer-NOE NMR experiments of the constrained peptides in the presence and absence of NF-YB/C dimer revealed that the α-methyl group caused the N-terminus of the peptide to deviate considerably from its bound form. 70 The thermodynamic parameters for binding reflect the structural differences; the fully α-methylated variant exhibited a reduced entropic cost of binding which was countered by a decrease in binding enthalpy, whereas the stronger binding mono-methylated variant had a much more unfavourable entropy of binding that was compensated by a large enhancement in binding enthalpy. Such results underscore the importance of biophysical and structural considerations in the development of potent peptidomimetic PPI inhibitors.…”
Section: Enhancing Protein Binding Affinitymentioning
confidence: 99%
“…Successful examples of a peptide excision strategy applied to the generation of all‐hydrocarbon stapled peptides include: stapled peptides which block the helix‐helix interfaces found in the coiled‐coil region of the gp41 protein with potent anti‐viral activity against HIV‐1; [ 67 ] stapled peptides which mimic the junction domain of Plasmodium falciparum calcium‐dependent protein kinase 1 ( Pf CDPK1; Figure 3B) to disrupt J‐domain binding and provide allosteric inhibition of Pf CDPK1 activity, blocking malarial parasite development; [ 66 ] stapled peptides extracted from the dimerization interface of bone morphogenetic protein‐2 (BMP‐2) which is a possible target for bone repair therapies; [ 68 ] stapled peptides which target the nuclear transcription factor NF‐Y, a therapeutic target implicated in various diseases such as cancers and neurodegeneration. [ 69 ] Clearly, the success of these strategies has relied on the availability of crystallographic data and amino acid building blocks to readily synthesize stapled peptide sequences.…”
Section: Section 1: Defining the Primary Sequencementioning
confidence: 99%